REPRESENTASI MATEMATIS SISWA TUNANETRA DALAM MEMAHAMI KONSEP SEGITIGA BERDASARKAN TEORI VAN HIELE - Anggreini, Dinar Adi; Setiawan, Toto Bara; Oktavianingtyas, Ervin (Department of Mathematics Education , University of Jember, 2017)
Abstract. Mathematical representation is an ability of people to re-express their interpretation about their understanding of a problem. In the practice of learning, students frequently could not represent their own mathematical interpretation. It is caused by many factors, for instance, physical limitations owned by students with visual impairment. In this study, it would be described about mathematical representative in the form of written text, mathematical expressions, verbal representations, and visual representation in understanding the concept of triangles. Therefore, the type of the research is decriptive research with qualitative approach. The subject of the study is 3 students with visual impairment in VII grade in SMPLB-A TPA Jember. The description of mathematical representation of blind students are adjusted to the level of thinking based on Van Hiele theory. Van Hiele divides students' level of thinking into 5 levels: visualization, analysis, informal deduction, deduction, and rigor. The three subjects conduct test of thinking level based on Van Hiele theory, mathematical representation test, and interview. The level category of students’s thinking is figured out through Van Hiele theory. Mathematical representation test is used to comprehend mathematical representation by using written text which containst the written explanation of the subjects towards the triangles and mathematical expression about how the subjects solve the problems of the triangles by using mathematical model. Meanwhile, the interview is used to know the verbal representation which contains the oral explanation about triangle concept and visual representation about how the subject creates the triangle. Keywords: Mathematical representation, visual impairment student, triangle, Van Hiele theory